STRATEGI PENGUATAN KARAKTER RASA INGIN TAHU PADA PESERTA DIDIK MELALUI PEMBELAJARAN SAINTIFIK DI SD CENDEKIA ISLAMIC SCHOOL KELAS IV - Adya Pribadi, Reksa; Mahdayana, Dea; Ramadhani Zahra, Zhaffa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This study aims to determine the strategy of strengthening curiosity as a trait using a scientific approach. The population of the study is among the 4th-grade students of SD Cendekia Islamic School. This study uses qualitative research methods and data collection techniques such as direct interviews with educators and observations in the learning process as well as documentation studies. Sources of data in this study are educators and students. The teaching activities of 4th graders at SD Cendekia Islamic School class IV have been carried out on a distance learning basis since the outbreak of covid-19 in Indonesia. The results of this research, conducted on fourth-grade students at SD Cendekia Islamic School, show that the learning activities carried out during the distance learning period were not optimal in terms of scientific approaches. Because, according to researchers, the use of a scientific approach, when face-to-face interaction with students is possible, is more efficient than its use in distance learning, which is the current situation. Hence, the researchers conclude that the study conducted during the distance learning process that utilized scientific approaches did not maximize strengthening curiosity as a trait. Researchers suggest that, in distance learning exercises, it is necessary to pay attention first to all components that can support the successful implementation of scientific approaches on the development of curiosity as a trait.